PENGARUH GREEN BANKING TERHADAP KINERJA KEUANGAN PERBANKAN DI INDONESIA (PERIODE TAHUN 2018-2022) - Mahardika, Putu Arya Diva; Fitanto, Bahtiar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Environmental problems include climate change, and an increase in the frequency of natural disasters have become widespread phenomena. These harmful trends have been aided by the absence of environmental considerations in banking operations. The idea of